Teaching a diverse primary curriculum - Doull, Karin (Learning Matters, 2022)
"Without conscious consideration of diversity in the curriculum, there is a danger that teachers fall back on a narrow syllabus. Trainee and new teachers need support to expand their knowledge and understanding of the curriculum to enable them to make active choices to ensure diversity in what they teach. This book explains why and how diversity can be taught through the primary National Curriculum. It includes practical examples of good practice and realistic straightforward ideas and resources to support new teachers to go into the classroom ready to bring diverse voices and learning to their teaching."